A CASE STUDY ON THE AYURVEDIC MANAGEMENT OF BAHUPITTA KAMALA WSR JAUNDICE - Saka, Vaishnavi Narahari; Chandurkar, Vivek S. (International Journal of Research -GRANTHAALAYAH, 2018)
Modern culture and advanced technology have made life comfortable, but it’s given invitation to many diseases. In fast life style of people are leading irregular eating habits, eating outside has become fashion which increased risk of contaminated food and water. All these etiological factors lead to risk of related disorders. Bahupitta kamla is one of important disease. Jaundice is a condition in which yellowness of skin, sclera, mucus membrane, and excretions occurs due to hyperbilirubinemia and depositions of bile pigments. Jaundice is described as kamala vyadhi in Ayurveda. IN ayurvedic samhita description of kamala is given in detail. The description of hepatocellular jaundice is similar to ayurvedic description of kamala vyadhi. Here a case report of a 30 years male having Bahupitta Kamala (Jaundice) who was treated with ayurvedic medicine and some panchakarma which give effective results with ayurvedic management.